2018
DOI: 10.1002/ase.1815
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of a Three‐Dimensional Tooth Morphology Quiz for Dental Students

Abstract: Tooth morphology has a pivotal role in the dental curriculum and provides one of the important foundations of clinical practice. To supplement tooth morphology teaching a three‐dimensional (3D) quiz application (app) was developed. The 3D resource enables students to study tooth morphology actively by selecting teeth from an interactive quiz, modify their viewpoint and level of zoom. Additionally, students are able to rotate the tooth to obtain a 3D spatial understanding of the different surfaces of the tooth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
39
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 80 publications
0
39
2
1
Order By: Relevance
“…They may be applied to different contexts or learning experiences, allowing students from different health fields to emphasize specific anatomical demands and relate differently to the digital technologies based on their background (Kenway and Bakr, 2018). When adapted to a context that involves flipped classrooms and blended‐learning concepts, they allow students to be more active and responsible for their learning process (de Azevedo et al, 2015; Kenway and Bakr, 2018; Lone et al, 2018, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They may be applied to different contexts or learning experiences, allowing students from different health fields to emphasize specific anatomical demands and relate differently to the digital technologies based on their background (Kenway and Bakr, 2018). When adapted to a context that involves flipped classrooms and blended‐learning concepts, they allow students to be more active and responsible for their learning process (de Azevedo et al, 2015; Kenway and Bakr, 2018; Lone et al, 2018, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] It has been found that quizzing is as an effective method of teaching to small group of students. 7 Cervical vertebral maturation is an important orthodontic topic for teaching to undergraduate dental students. There are several methods of analyzing cervical vertebral maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, neither Maggio et al 2012, nor Al-Thobity et al 2017included in their studies a comparison of digital 3D models with cadaveric teeth, which are considered as the best teaching modality (Cantin et al, 2015), as it was recognized by Lone et al (2019). In fact, could digital 3D models be superior to cadaveric teeth, since they were not proved clearly superior to other, less strong, teaching methods?…”
mentioning
confidence: 99%
“…It was our pleasure to read the article by Lone et al (2019), who developed and assessed a three-dimensional (3D) application for dental anatomy education. The authors concluded that the application was of equivalent educational value with extracted teeth, while they stated that computer-based 3D models enhance teaching outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation